Is Web-Based Diabetes Training Effective or Ineffective on the Quality of Life of Individuals with Type 2 Diabetes Mellitus?: A Systematic Review - Elyeli, Kemal; Esmaeilzadeh, Samineh; Bebis, Hatice (Springer, 2024)
Diabetes mellitus is called as the pandemic of the era due to its rising prevalence. Since it is a disease that affects all spheres of life, it has an impact on the quality of life of individuals. This systematic review aims to examine the effect of web-based diabetes training programmes prepared for individuals with type 2 diabetes mellitus on their quality of life. The PRISMA-P (Preferred Reporting Items for Systematic Review and Meta Analysis Protocols) flowchart was used in the literature search stage. A comprehensive search was performed through the [MeSH] keywords (Web-based Intervention, Randomised Controlled Trial, HRQOL, Type 2 Diabetes) until May 8, 2024 in databases of PubMed, Web of Science, Science Direct, Medline, CINAHL, EBSCO host, Cochrane Library, and Google Scholar. Zotero software program was used to identify duplications of the obtained studies. Seven randomised controlled studies were included in the review. It was found that, most of the studies that were included in review showed that quality of life did not cause any significant difference in the level of quality of life; whereas, improvement was observed in quality-of-life levels in all of the experimental groups. Also, studies conducted for 1.5 to 3 months showed that web-based training was effective in improving the quality of life. Consequently, it is recommended that web-based trainings be long enough to prevent patients from dropping out of training, with possibility of an online individual interview, and follow-up periods of 1.5 to 3 months in order to achieve effective results. PROSPERO Number: CRD42024530777.
Keywords: Web-based intervention; Randomized controlled trial; Health-related quality of life; Type 2 diabetes mellitus; Systematic review